Physiological changes and hydrolyzing enzyme activities during ripening of guava (Psidium guajava) fruits on-tree and in-storage - SHARMA, ARTI; SHARMA, R K; SIDDIQUI, SALEEM; HAZARIKA, T K (The Indian Journal of Agricultural Sciences, 2017)
An investigation was made to compare various physiological changes and hydrolyzing enzyme activities of guava (Psidium guajava L.) fruits of cv. Hisar Surkha and Hisar Safeda during ripening on-tree and in-storage. For studying on-tree ripening, fruits were harvested from both winter and rainy season crop at green mature, half ripe and full ripe stages. However for in storage ripening studies, fruits were harvested at green mature stage. Studies showed a progressive decrease of moisture content of fruits with advancement of ripening both on-tree and in-storage, whereas, specific gravity of fruits exhibited an inconsistent trend during ripening on-tree but followed a continuous decreasing trend during ripening in-storage. A continuous chlorophyll degradation and carotenoid synthesis was exhibited with the advancement of ripening on-tree as well as in-storage. Activities of enzyme PPO increased with advancement of ripening on-tree as well as in-storage. Catalase activity showed a sigmoidal trend during ripening of guava fruits both on-tree and in-storage, i.e. initially increased and thereafter followed a declining trend. Changes in the activities of both the enzymes were faster during ripening in-storage as compared to ripening on-tree. The changes were faster in cv. Hisar Surkha than Hisar Safeda. Activities of both the enzymes were higher in winter season crop as compared to rainy season crop.